2021
DOI: 10.1002/suco.202100354
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of compressive strength of geopolymer concrete using machine learning techniques

Abstract: Geopolymer concrete (GPC) is the result of an inorganic polymerization reaction that takes place in presence of an alkaline medium in the materials such as fly ash and slag, which are rich in silicates and aluminates. In this study, an artificial neural network (ANN), multiple linear regression, and the multivariate nonlinear regression (MNLR) models were designed to predict the 28 days compressive strength of the GPC. To train the models, a total of 289 data sets were used, which were published by different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 105 publications
(230 reference statements)
0
41
0
Order By: Relevance
“…Their results indicated that the hybrid MFA-ANN model accurately predicted compressive and tensile strengths in concrete. Although many optimization techniques have been applied in various fields regarding cementitious materials [31][32][33][34] and structure, 35,36 developing other optimization algorithms such as ACO, PSO, and biogeographybased optimization 37 (BBO) may be of interest to determine the optimization parameters in ANN training.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the hybrid MFA-ANN model accurately predicted compressive and tensile strengths in concrete. Although many optimization techniques have been applied in various fields regarding cementitious materials [31][32][33][34] and structure, 35,36 developing other optimization algorithms such as ACO, PSO, and biogeographybased optimization 37 (BBO) may be of interest to determine the optimization parameters in ANN training.…”
Section: Introductionmentioning
confidence: 99%
“…63 When used to predict the compressive strength of geopolymer concrete, the ensemble ML techniques boosting and AdaBoost (AdB) demonstrated a high value of R 2 equal to 0.960 and 0.930, respectively. 64 Recently, Gupta et al 65 developed ANN model containing two hidden layers for predicting the compressive strength of geopolymer, the ANN model can be achieved with high performance R 2 = 0.904 for testing datasets. Different investigations of ML model application for predicting compressive strength of geopolymer concrete is summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The three‐layer Bayesian‐regularized ANN model with 10 neurons in every layer, according to the study, is the best model for estimating Geo‐p concrete CS ( R = 0.99 and MSE = 1.017). Gupta and Rao 30 used multivariate nonlinear regression, multiple linear regression, and ANN to estimate the CS of Geo‐p concrete 31 . Khan et al 31 used ANN, ANFIS, multi‐gene expression programming (MEP) to estimate the CS and thermal conductivity of hemp‐based bio‐composites.…”
Section: Introductionmentioning
confidence: 99%